Pengembangan Modul Berpendekatan Pembelajaran Science Technology Engineering And Mathematic Pada Materi Keanekaragaman Hayati Untuk Meningkatkan Kreativitas: (Module Development Approaching Science Technology Engineering And Mathematical Learning on Biodiversity Materials to Increase Creativity) - Agung Laksono; M. Rusdi; Tedjo Sukmono (BIODIK, 2021)
Module development is a process of developing procedural knowledge in creating meaningful learning. Learning is developed to obtain multidisciplinary learning, student-centered, active and critical, changes in interactive learning patterns. In the learning process with a STEM approach, information is formed through collaboration and creativity. Students use skills and learning processes in science, technology, engineering, and mathematics in their thinking processes to solve problems. This development aims to determine procedures, designs, student responses and teacher assessments in increasing creativity. Development of the biodiversity module with the STEM approach using the Project Based Learning model on biodiversity material in SMA Negeri 2 Jambi City by adapting the ADDIE model. The research instruments used were interview sheets, open and closed questionnaires, and a daily log. The product developed is a Biodiversity Module with a STEM approach. The module was validated by three teams of experts and declared feasible then the teacher's assessment had a kappa value of 0.74 in a good category. The results of one-on-one trials for project one have a percentage of 82.08% in the category of "Very feasible" and project two have a percentage of 89.05% with the category "Very feasible". The results of the small group trial had a kappa value for project one of 0.81 which was in the very good category and for project two had a kappa value of 0.42 in the medium category. Based on the results of the observations of two teachers on project one in increasing the creativity of students, it has a kappa value of 0.74 with a good category. Based on the results of the study, it was concluded that the module with the STEM approach was categorized as good so that it could increase the creativity of students, and the module with the STEM approach was suitable for use as a media for learning biology. Abstrak. Pengembangan modul merupakan proses pengembangan pengetahuan prosedural dalam menciptakan pembelajaran yang bermakna. Pembelajaran dikembangkan guna memperoleh pembelajaran yang bersifat multidisiplin ilmu, berpusat kepada peserta didik, aktif dan kritis, perubahan pola pembelajaran interaktif. Pada proses pembelajaran berpendekatan STEM informasi dibentuk melalui kolaboratif dan kreativitas. Peserta didik menggunakan keterampilan dan proses belajar dalam ilmu pengetahuan, teknologi, teknik, dan matematika dalam proses berpikir untuk menyelesaikan permasalahan. Pengembangan ini bertujuan untuk mengetahui prosedur, desain, respon peserta didik dan penilaian guru dalam meningkatkan kreativitas. Pengembangan modul kenakaragaman hayati dengan berpendekatan STEM menggunakan model Project Based Learning pada materi Keanekaragaman hayati di SMA Negeri 2 Kota Jambi dengan mengadaptasi model ADDIE. Instrumen penelitian yang digunakan adalah lembar wawancara, angket terbuka dan tertutup, dan daily log. Produk hasil pengembangan berupa Modul Keanekaragaman hayati berpendekatan STEM. Modul divalidasi oleh tiga tim ahli dan dinyatakan layak kemudian penilaian guru mempunyai nilai kappa 0,74 dengan kategori baik. Hasil ujicoba satu-satu untuk proyek satu mempunyai persentase 82,08% dengan kategori â€œSangat Layakâ€ dan proyek dua mempunyai persentase 89,05% dengan kategori â€œSangat Layakâ€. Hasil ujicoba kelompok kecil mempunyai nilai kappa untuk proyek satu 0,81 dengan kategori sangat baik dan untuk proyek dua mempunyai nilai kappa 0,42 dengan kategori sedang. Berdasarkan hasil observasi dua guru terhadap proyek satu dalam meningkatkan kreativitas peserta didik mempunyai nilai kappa 0.74 dengan kategori baik. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa Modul berpendekatan STEM dengan kategorikan baik sehingga dapat meningkatkan kreativitas peserta didik, dan modul berpendekatan STEM layak digunakan sebagai media pembelajaran Biologi.